2013
DOI: 10.1093/jrr/rrs135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic hypoxia and radiation quality on cell survival

Abstract: To investigate the influence of chronic hypoxia and anoxia on cell survival after low- and high-LET radiation, CHO-K1 cells were kept for 24 h under chronic hypoxia (94.5% N2; 5% CO2; 0.5% O2) or chronic anoxia (95% N2; 5% CO2). Irradiation was performed using 250 kVp X-rays or carbon ions with a dose average LET of 100 keV/μm either directly under the chronic oxygenation states, or at different time points after reoxygenation. Moreover, the cell cycle distribution for cells irradiated under different chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 28 publications
(27 reference statements)
5
62
0
Order By: Relevance
“…Based on experimental data, it has also been suggested that chronically hypoxic cells might be more sensitive than acutely hypoxic cells [38–40]. The present study, however, does not take into account the difference in sensitivity between the two types of hypoxic cells, since they cannot yet be distinguished in vivo .…”
Section: Discussionmentioning
confidence: 86%
“…Based on experimental data, it has also been suggested that chronically hypoxic cells might be more sensitive than acutely hypoxic cells [38–40]. The present study, however, does not take into account the difference in sensitivity between the two types of hypoxic cells, since they cannot yet be distinguished in vivo .…”
Section: Discussionmentioning
confidence: 86%
“…Asynchronously growing cells showed for low doses an OER similar to that in G1 which increased with decreasing survival levels to a value near that of S-phase cells. The slightly different behavior of our two measured cell lines may then be due to differences in the cell cycle distribution: RAT-1 cells had an averaged cell cycle distribution of 58% G1, 22% S and 20% G2/M, while CHO were 34% in G1, 50% in S and 16% in G2/M [33]. The higher number of S-phase cells could thus explain the greater difference in OER values for CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple realms of research have unveiled a few signaling pathways that contribute to resistance to IR. Among them, hypoxia pathway was one of the most extensively studied pathways, due to its intimate association with ionizing conditions [26][27][28]. Here, we demonstrated that quercetin could sensitize keloid fibroblasts to IR treatment, and the effect was associated with expression of HIF-1α, a critical component of radioresistance related hypoxia pathway.…”
Section: Discussionmentioning
confidence: 68%